Emergence Delirium in a 29-Year-Old Man following an Uneventful Appendectomy - Zhi Wang; Yong Yang; Yang Chen; Kai Lu; Bing Chen (Case Reports in Medicine)
Emergence delirium (ED) is defined as the delirium that occurs during the transition from the sleep state to full consciousness. ED increases the risk for injury, self-extubation, hemorrhages, and prolonged hospitalization and occurs in patients of any age but most often in children and elderly patients. However, ED in young adults is rarely reported. We presented a case of typical ED occurring in a young healthy man following an uneventful appendectomy. The causes of ED can be classified as either predisposing or precipitating factors. In this case, the unnoticeable mental stress may be the predisposing factor and the sevoflurane maintenance of anesthesia may be the precipitating factor. ED occurs at any age of patient and in any minor surgery, and anesthesiologists should do some work to prevent it from happening.